The relevance of coastal sediment budgets to management of sandy wave-dominated shorelines, a case study of Twofold Bay, southeastern Australia. (1st September 2022) - Oliver, Thomas S.N.; Tamura, Toru
Abstract: Coastal compartments provide a framework for considering sediment budgets by defining the boundaries between adjacent beaches or sections of coast with a common sediment source. Here we present Twofold Bay as an ideal field laboratory to test the coastal compartment management approach, and in particular, note the relevance of long-term coastal evolution to shorter term planning timescales. Twofold Bay on the New South Wales south coast, Australia, contains four main beaches (Aslings, Boydtown, Whale and Fisheries Beaches) and associated barrier systems. We present a range of existing geological and geomorphic information combined with new field data which demonstrate considerable variation in the Holocene evolution and sediment budget of these adjacent beaches. These data show three broad sediment types exist within Twofold Bay and its beach systems: Type 1 is a mature quartz-rich sand derived from the shelf. Type 2 is a fine carbonate-rich sand from local biogenic production, and Type 3 is a coarse-fine angular feldspathic sand sourced from the Towamba River which drains to Twofold Bay via the southern end of Whale Beach. Newly available high-resolution topography and bathymetry as well as sediment thickness maps, have enabled shoreface geometry and basement topography to be estimated seaward of each beach and reveal considerable variability between sites helping explain past shoreline behaviour. Several new optically stimulated luminescence (OSL) ages for Boydtown Beach, combined with existing ages, confirm two distinct phases of shoreline progradation, initially at 0.16 m/yr, and then over the past ∼1500 years, at 0.65 m/yr. The increase in progradation rate reflects sediment supply from the Towamba River via Whale Spit. While these two beaches have become interconnected, Aslings Beach and Fisheries Beach are dominated by sediment Type 1 and Type 2 respectively and have different evolutionary histories with Aslings Beach forming a stationary barrier while Fisheries has prograded at 0.15 m/yr over the past ∼4300 years according to a new set of OSL ages. The Holocene evolution of these four adjacent beaches has resulted from their differing sediment sources and budgets and is in accord with several available datasets of decadal shoreline changes. These results demonstrate that spatial variation in shoreline behaviour is driven by differences in sediment budget and that just as adjacent beaches have behaved differently in the past, so will they in the future. Understanding these drivers of shoreline change is imperative to effective coastal management and planning in the context of projected future sea-level rise and other anthropogenic pressures. Highlights: Barrier evolution, shoreface geometry and sedimentology indicate sediment budget. Different sources of sediment are responsible for coastal barrier formation. Recent shoreline changes broadly reflect longer Holocene history. Adjacent beaches may respond differently to the same boundary conditions. Coastal managers should regard sediment budgets as key drivers of shoreline change.